Transcranial ultrasound stimulation parameters for neurological diseases: a systematic review - Wang, Jingxuan; Wang, Hujun; Jiang, Tingyu; Wang, Yingpeng; Li, Ning; Qie, Shuyan (Frontiers in Neurology, 2025)
BackgroundTranscranial ultrasound stimulation (TUS) is a non-invasive neuromodulation technique with promising clinical potential. Its therapeutic efficacy and safety are significantly influenced by stimulation parameters. This study investigates how various stimulation parameters modulate human brain function, offering insights for optimizing stimulation protocols to improve clinical and research outcomes.MethodsA comprehensive literature search was conducted across the Medline-PubMed, Web of Science, Medline-Ovid, Embase, EBSCOhost, Cochrane Library, CNKI, WanFang, and VIP databases using the keyword “transcranial ultrasound stimulation,” covering publications up to September 24, 2024. Two researchers independently screened articles according to predefined inclusion and exclusion criteria. Extracted data included article details, demographic information, interventions, study design, data analysis, and results. The risk of bias was assessed using the RoB2 and ROBINS-I tools. Multiple linear regression analysis explored the relationship between TUS parameters and human physiological responses.ResultsThirty-five studies were included, consisting of 10 randomized controlled trials and 25 other studies, involving 664 participants (over 34% female) aged 10 to 90 years. Eighteen studies used focused transcranial ultrasound (fTUS), six used non-focused TUS (no-fTUS), and 11 used transcranial pulse stimulation (TPS). Fundamental frequencies ranged from 220 to 650 kHz, and spatial peak pulse average intensities (ISPPA) ranged from 0.5 to 31 W/cm2. Frequency, pulse repetition frequency, and mechanical index showed significant effects (p < 0.05).ConclusionTUS demonstrates disease-specific therapeutic potential, with low-frequency protocols targeting neurodegenerative disorders and high-frequency parameters effectively alleviating motor symptoms. Core parameters (fundamental frequency, pulse repetition frequency, mechanical index) modulate neuroplasticity-driven outcomes, accompanied by mild transient adverse effects (incidence < 5%). Large-scale randomized trials integrating multimodal navigation are required to standardize dose-response frameworks and refine spatial targeting for clinical translation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier: CRD42024601735.